Uncovering the theoretical underpinnings of an interprofessional preschool intervention program: Tumbling Together: Découvrir les fondements théoriques du programme d'intervention interprofessionnelle préscolaire : Tumbling Together. (February 2015) - Eamer, Claire R.; Lefebvre, Pascal; Ducharme, Daphne A.
Background: Intervention programs are rarely tailored for children with self-regulation and communication challenges. Therefore, clinicians develop their own programs as is the case with the preschool program Tumbling Together. This program combines occupational therapy, speech-language therapy, and gymnastics. Purpose: The aim of this study was to take an in-depth look at the program to answer the following questions: (a) What are the fundamental concepts of the program? and (b) What is the underlying theoretical model that illustrates the relationships between concepts? Method: The qualitative research method of grounded theorizing using situational analysis was employed. Findings: Fourteen main concepts of the program were identified and informed the development of a theoretical model. Implications: A theoretical model incorporating Tumbling Together's concepts is a first step in evaluating its efficacy. Although the concepts involved are not novel, their unique combination forms a promising intervention approach for this population. Description: Les programmes d'intervention sont rarement adaptés aux enfants ayant des problèmes d'autorégulation et de communication. Cependant, les cliniciens conçoivent leurs propres programmes, comme dans le cas du programme préscolaire Tumbling Together. Il s'agit d'un programme combiné d'ergothérapie, d'orthophonie et de gymnastique. But: Le but de cette étude était d'examiner le programme en profondeur afin de répondre aux questions suivantes : (1) Quels sont les concepts fondamentaux du programme? et (2) Quel est le modèle théorique sous-jacent qui illustre les relations entre les concepts? Méthodologie: La méthode de recherche qualitative qui consiste à élaborer une théorie fondée sur les données à partir d'une analyse situationnelle a été utilisée. Résultats: Les quatorze principaux concepts du programme ont été identifiés et ont permis d'orienter l'élaboration d'un modèle théorique. Conséquences: Le modèle théorique incorporant les concepts du programme Tumbling Together constitue la première étape de l'évaluation de son efficacité. Bien que les concepts en jeu ne soient pas nouveaux, leur combinaison unique constitue une méthode d'intervention prometteuse pour cette population.